Age Estimation Through Radiographs (International Journal of Innovative Research in Computer Science & Technology, 2022)
The skeleton is an important part of the human body. It provides a definite shape and definesthe  stature of the human body along with it also plays an  important role in forensic science. It aids forensic  anthropologists in determining the age, sex and post  mortem interval of the deceased person, if only the skeletal  remains are found. This article reviews the techniques used  for age estimation from different bones of human body.  Forensic anthropologyis study of human skeletal remains to help determine the identity of the missing persons andto  estimate time since death and age. There are various bones  which help to determine the age range of the deceased like skull, clavicle and the pelvisregion. Radiographic methods arehelpful in examining these bones. There are around 300  bones present in a new born and as a person grows these  bones start to fuse. At the age of 40 years all the bones fuse  to make atotal of 206 bones. Bones start to ossify as the  person ages and hence by studying the ossification of bones we can determine an age range for a person.
Keywords: Age Estimation; Forensic Anthropologists; Forensic; Radiographic Methods